Impact of cyanosis on ventilatory responses during stair climb exercise in Eisenmenger syndrome and idiopathic pulmonary arterial hypertension. (15th October 2021) - Samaranayake, Chinthaka B.; Warren, Christopher; Siewers, Karina; Craig, Stuart; Price, Laura C.; Kempny, Aleksander; Dimopoulos, Konstantinos; Gatzoulis, Michael; Hopkinson, Nicholas S.; Wort, Stephen J.; Hull, James H.; McCabe, Colm
Abstract: Studies assessing exercise ventilatory responses during real-life exercise in pulmonary arterial hypertension (PAH) which include patients with cyanotic congenital heart disease are scarce. We assessed the ventilatory response to stairclimbing in patients with idiopathic PAH (IPAH) and congenital heart disease-associated PAH with Eisenmenger (EIS) physiology compared to healthy controls. Fifteen adults with IPAH, six EIS and 15 age and body mass index (BMI) matched controls were prospectively recruited. Participants completed spirometry and a self-paced stair-climb (48 steps) with portable cardiopulmonary exercise testing (CPET) equipment in-situ. Borg dyspnoea scores were measured at rest and on stair-climb cessation. Both IPAH and EIS groups had amplified ventilatory responses compared to Controls. The rate of increase in minute ventilation (VE) was exaggerated in EIS driven by an early increase in tidal volume (Tv) and more gradual increase in respiratory rate (RR). Peak Tv, RR, Tv: forced vital capacity (FVC) ratio, VE/VCO2 slope and stairclimb duration were significantly higher in EIS and IPAH compared to controls despite similar baseline spirometry and change in oxygen uptake on exercise. A decline in end-tidal carbon dioxide (CO2 ) and arterial oxygen saturations in early exercise distinguished EIS and IPAH patients. Significant correlations were observed between peak exercise Borg score and stair-climb time ( r  = 0.73, p  = 0.002), peak end-tidal CO2 ( r  = −0.73, p  = 0.001), peak VE ( r  = 0.53, p  = 0.008), peak RR ( r  = 0.42, p  = 0.011) and VE/VCO2 slope ( r  = 0.54, p = 0.001). Patients with IPAH and EIS have exaggerated ventilatory responses to stair-climbing compared to the controls with more severe levels of dyspnoea perception in Eisenmenger syndrome for equivalent oxygen uptake and work. Highlights: Ventilatory response during daily activity can help us to understand mechanisms of dyspnoea in pulmonary hypertension (PAH). Portable cardiopulmonary exercise test equipment was used during stairclimbing to assess ventilation in patients with PAH. Patients with Eisenmenger physiology and idiopathic PAH experience excessive ventilatory demand irrespective of oxygen uptake. Strategies to optimise respiratory mechanics with exercise retraining may therefore be of benefit in these patient subgroups.